PENINGKATAN PENGETAHUAN TENTANG TANAMAN HERBAL TOGA SEBAGAI TERAPI GASTRITIS SISWA SMK IBRAHIMY 1 P2S3 SITUBONDO: INCREASING KNOWLEDGE ABOUT THE TOGA HERBAL PLANT AS A THERAPY FOR GASTRITIS FOR STUDENTS OF IBRAHIMY 1 P2S3 SITUBONDO VOCATIONAL SCHOOL - Burhanudin gasim soka; Nurdiana Kholidah (Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Family Medicinal Plants (TOGA) are nutritious plants planted in yards and fields and managed by families. The types of plants grown fulfill the family's need for traditional medicines that can be made by themselves. The medicinal plants chosen are usually plants that can be used for first aid. The presence of medicinal plants in the home environment is very important, especially for families who do not have easy access to medical services such as clinics, health centers or hospitals. Each family can cultivate medicinal plants independently and use them so that the principle of independence in family medicine will be realized. The method used is counseling, distributing leaflets, asking questions and distributing questionnaires. The aim of the activity is to increase knowledge regarding herbal plants used for gastritis therapy, the importance of maintaining health as a prophylaxis, especially for gastritis which can cause other diseases and cultivating herbal plants. The results obtained were that the majority of respondents were 18 years old at 27.8%, the respondents' education was class After delivering the material the results showed that 90.28% knew TOGA. The usefulness of the activity for participants was 94.44%.